Impact of Current, Defense and Development Expenditure on Economic Growth of Pakistan - Dur e Muqadas; Muhammad Niamat Ullah Babar; Sanaullah Khan; Faridullah Khan; Ruqia Naaz; Muhammad Ehsan Elahi; Muhammad Waqar; Bushra Zaman; Saima Munir; Shehla Mazhar (Journal for Social Science Archives, 2025)
The present study aimed at investigating the impact of current, defense and development Expenditure on economic growth of Pakistan over period of time 1994-95 to 2020-21. In this regard, econometric techniques i.e Augmented Dicky Fuller Unit Root Test, Ordinary Least Square Test, Auto-regressive Distributive Lag Model, Bound Test and Error Correction Models were applied. The result findings revealed that Defense Expenditure significantly influenced economic growth of Pakistan. Bound Test witnessed log run relationships exist between tested variables in the model. Findings of Error Correction Model provided F-Stat value as 6.8 which is higher than upper and lower limit revealing speed of adjustment from short run dynamics towards long run equilibrium. Author recommends as policy implications that special emphasis needs to be paid in utilizing current and developmental expenditure for ensuring aggregate demand exclusively so necessary for accelerating economic growth in Pakistan.